2020
DOI: 10.1016/j.xphs.2019.09.018
|View full text |Cite
|
Sign up to set email alerts
|

An Industry Perspective on Forced Degradation Studies of Biopharmaceuticals: Survey Outcome and Recommendations

Abstract: The BioPhorum Development Group is an industry-wide consortium enabling networking and sharing of common practices for the development of biopharmaceuticals. Forced degradation studies (FDSs) are often used in biotherapeutic development to assess criticality of quality attributes and in comparability studies to ensure product manufacturing process consistency. To gain an understanding of current industry approaches for FDS, the BioPhorum Development GroupeForced Degradation Point Share group conducted an inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…Halley et al. conducted an intercompany benchmarking survey and reported an overview of the common practices used to perform forced degradation studies [97]. Since Fc‐fusion proteins possess a large structural heterogeneity and complexity, no specific stress and no generic conditions could be advised.…”
Section: Analytical Methods For Fc‐fusion Proteins Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…Halley et al. conducted an intercompany benchmarking survey and reported an overview of the common practices used to perform forced degradation studies [97]. Since Fc‐fusion proteins possess a large structural heterogeneity and complexity, no specific stress and no generic conditions could be advised.…”
Section: Analytical Methods For Fc‐fusion Proteins Characterizationmentioning
confidence: 99%
“…There are many available options to perform forced degradation studies, such as different materials, conditions, number and duration of time points, as well as several analytical methods to evaluate the results of the applied stress. Halley et al conducted an intercompany benchmarking survey and reported an overview of the common practices used to perform forced degradation studies [97]. Since Fc-fusion proteins possess a large structural heterogeneity and complexity, no specific stress and no generic conditions could be advised.…”
Section: Forced Degradation Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To avoid further decomposition, the degraded sample is then neutralized using suitable acid, base, or buffering. [37][38] Drug substance of oxidative degradation involves a mechanism for the electron transfer to form reactive anions and cations. Hydrogen peroxide is widely used in forced degradation studies for the oxidation of drug substances but other oxidizing agents such as metal ions, oxygen, and radical initiators may also be used.…”
Section: In the Pre-ind Periodmentioning
confidence: 99%
“…Alternatively, Pikal et al noted that for FD Human Growth Hormone at 40 • C, there was a linear relationship between moisture content and aggregation rather than a bell-shaped distribution [14]. Guidelines for use when developing stressing strategies for biotechnology products have been published [15] and industrial stressing conditions have also been reviewed [16,17]. During long-term storage, the sugar excipient used in the formulation, moisture content and temperature can all affect the physical and chemical stability of FD cakes.…”
Section: Introductionmentioning
confidence: 99%